MAKNA DENOTASI, KONOTASI, DAN MITOS DALAM IKLAN SK-II “THE CHANGE DESTINY”: ANALISIS SEMIOTIKA RONALD BARTHES - Nurindah Raniah Hadi; Firra Zakia Hasibuan; Azrin Ahda Sabilla; Muhammad Tamamul Iman (SOSFILKOM : Jurnal Sosial, Filsafat dan Komunikasi, 2025)
This study analyzes the denotative, connotative, and mythological meanings in the SK-II “The Change Destiny” advertisement using Roland Barthes' semiotic approach. Advertisements are understood as a space for the production of meaning that shapes perceptions of female beauty and identity within modern visual culture. Through an analysis of visual elements such as facial expressions, colors, gestures, and symbolic scenes for example, removing jewelry, wiping off lipstick, and moving toward the light. The study finds that the advertisement presents a narrative of women's transformation from social pressure to self-liberation. At the mythical level, the advertisement constructs a discourse that true beauty stems from the courage to make choices and accept oneself, rather than from beauty standards established by patriarchal culture. Thus, the SK-II “The Change Destiny” advertisement not only offers an image of beauty but also conveys an ideological message about women's empowerment and a shift in perspectives on modern beauty.